Organizing Students’ Independent Work under the Guidance of a Foreign Language Teacher at the University - Assylbekovna Zhetpisbayeva, Bakhytgul; Revovna Ospanova, Bikesh; Muratovna Baideldinova, Gulmira; Amantayevna Azimbayeva, Zhanat; Akynzhanovna Akynzhanova, Alma (Opción, 2019)
The article examines the actual problem of undergraduate students’ poor proficiency in foreign languages at non-linguistic universities. The purpose of this article is to develop and to test a technology for organizing students’ independent work under the guidance of a teacher of foreign language at a technical university, facilitating their perception of profession-oriented in- formation. The study was based on the existing technology and the devel- oped by us technology of organizing students’ independent work under the guidance of a teacher in teaching English as a foreign language in the first year at a polytechnic university. The study involved two groups: the con- trol group was engaged in the existing technology of organizing students’ independent work under the guidance of a teacher, and the experimental group had classes on the developed by us technology of organizing students’ independent work under the guidance of a teacher. As a result of the work carried out at the developed by us technology of organizing students’ inde- pendent work under the guidance of a teacher which mandatory component is authentic foreign texts in specialties,special profession-oriented tasks for simple common texts of a foreign language and controlling-measuring profession-oriented materials, it was revealed that the proposed profession-oriented technology of organizing students’ independent work under the guidance of a teacher contributed to better proficiency and understanding of profession-oriented texts by stu- dents of technical specialties.